Urbanisation reshapes gendered engagement in land-based livelihood activities in mid-sized African towns. (June 2020) - Shackleton, C.M.; Drescher, A.; Schlesinger, J.
Highlights: Urbanisation results in marked changes in livelihood activities. We reported land-based livelihood activities of 1156 households in and around 6 towns in 5 African countries. We assessed change in land-based activities in relation to gender of household head. Although urbanisation was associated with lower participation in land-based activities, over 90% of households did so. Differences in participation rates by female- and male-headed households narrowed with urbanisation. Abstract: Most sub-Saharan African countries are experiencing accelerating rates of urban migration, which bring with it many opportunities and challenges for migrating households, urban planners, governments and local and national economies. At the household level urbanisation may drive changes in the allocation of household labour and consequently social and economic relations. Yet how these are manifest in land-based livelihood strategies of arable cropping, livestock husbandry and the collection of wild products in urban settings has rarely been considered. Here we examine the changing participation rates in land-based livelihood activities by male- and female-headed households along the rural–urban continua of six sub-Saharan African secondary towns. To capture the gendered changes in land-based livelihood strategies along the urban–rural continuum, 1156 randomly selected households were sampled along transects radiating out from the urban through the periurban to rural surrounds. Participation in different land-based livelihood strategies was recorded by means of a questionnaire. We show that engagement in one or more land-based livelihood activities is widespread (92% of all households), even amongst urban households (82%). We also show that there are marked changes in gendered participation for many land-based activities along the urbanisation gradient, with a general narrowing of differences in participation rates between male- and female-headed households with increasing urbanisation. These results indicate that land-based activities are components of not only rural livelihoods in Africa, but are also practiced by most urban households too, and that urbanisation reshapes some of the gendered dimensions of roles more typical of rural contexts.